CMV driven CD8+ T-cell activation is associated with acute rejection in lung transplantation - Roux, Antoine; Mourin, Gisèle; Fastenackels, Solène; Almeida, Jorge R.; Iglesias, Maria Candela; Boyd, Anders; Gostick, Emma; Larsen, Martin; Price, David A.; Sacre, Karim; Douek, Daniel C.; Autran, Brigitte; et al. (Clinical immunology (Orlando, Fla.), 2013)
Lung transplantation is the definitive treatment for terminal respiratory disease, but the associated mortality rate is high. Acute rejection of the transplanted lung is a key determinant of adverse prognosis. Furthermore, an epidemiological relationship has been established between the occurrence of acute lung rejection and cytomegalovirus infection. However, the reasons for this association remain unclear. Here, we performed a longitudinal characterization of CMV-specific T-cell responses and immune activation status in the peripheral blood and bronchoalveolar lavage fluid of forty-four lung transplant patients. Acute rejection was associated with high levels of cellular activation in the periphery, reflecting strong CMV-specific CD8+ T-cell activity post-transplant. Peripheral and lung CMV-specific CD8+ T-cell responses were very similar, and related to the presence of CMV in the transplanted organ. These findings support that activated CMV-specific CD8+ T-cells in the lung may play a role in promoting acute rejection. •Acute rejection is associated with cellular activation in lung transplant patients.•High cellular activation reflects strong CMV-specific CD8+ T-cell activity.•Peripheral and lung CMV-specific CD8+ T-cell responses are related.•Activated CMV-specific CD8+ T-cells in the lung may promote acute rejection.